Fructose metabolism and its role in pig production: A mini-review - Xie, Jiahao; Shi, Shiyi; Liu, Yucheng; Wang, Shaoshuai; Rajput, Shahid Ali; Song, Tongxing (Frontiers in Nutrition, 2022)
Epidemiological studies have shown that excessive intake of fructose takes much of the blame for the increasing incidence of non-alcoholic fatty liver, obesity, and diabetes. However, depending on the amount of fructose consumption from diet, the metabolic role of fructose is controversial. Recently, there are increasing studies reported that diets low in fructose expand the surface area of the gut and increase nutrient absorption in mouse model which is widely used in fructose-related studies. However, excessive fructose consumption spills over from small intestine into liver for steatosis and execrates the colon cancer. Therefore, suitable animal models may be vitally concerned for studying fructose-induced metabolic changes. Along with the main global meat production, pig is well-known as a biomedical model at an advantage over murine and other animal models including similar nutrition and metabolism to human in anatomical and physiological aspects. Here, we review the characteristics and metabolism of fructose and summarize observations of fructose in pig reproduction, growth and development as well as acting as a human biomedical model. This review highlights fructose metabolism from intestine to blood cycle and presents the critical role of fructose in pig, which likely provide new strategies for curbing human metabolic diseases and promoting pig production.